Iodine-stained fragmented thromboembolism. Issue 6 (December 2019) - Hsu, Charlie Chia-Tsong; Watkins, Trevor; Kato, Kosuke; Fomin, Igor; Hapugoda, Sachintha; Cheng, Jeffery; Krings, Timo
Aim: Iodine-stained fragmented thromboembolism (ISFT) is a rare phenomenon encountered in the immediate aftermath of mechanical thrombectomy or rarely as a complication of post–carotid stenting. The aim was to describe the imaging appearance and discuss its pathophysiology. Method: This is a retrospective review of patients who underwent mechanical thrombectomy for acute stroke at a single institution over the period of one year. All patients underwent the standard acute stroke imaging protocol (CT head, CT angiogram (CTA) and CT brain perfusion) and when clinically appropriate followed by catheter angiogram and mechanical thrombectomy. ISFT was defined as an arterial luminal filling defect with Hounsfield density equal to or greater than iodine seen on the biplanar CT or conventional CT. The presence and location of ISFT were documented. Standard CT angiogram (CTA) or magnetic resonance angiogram (MRA) was performed 24–48 hours after the neurointerventional procedure to assess for recanalization, volume of infarction and the fate of the ISFT. Results: ISFTs were identified in eight (five males and three females, age range 18–80 years) out of 49 patients in the following locations: distal M1 ( n  = 1), M2 ( n  = 4), M3 ( n  = 1), A1 ( n  = 1), distal A2 ( n  = 1). ISFT and vessel recanalization occurred in five patients on follow-up. ISFT and vessel occlusion persisted in two patients. Conclusion: ISFT is likely the result of mechanical disruption of a thromboembolus, and porosity of the thromboembolus fragment may transiently retain iodinated contrast. Recognition of this entity may be important to aid detection of residual thromboembolism and avoid misinterpretation as calcified thromboembolism.